2017
DOI: 10.1158/1078-0432.ccr-17-1561
|View full text |Cite
|
Sign up to set email alerts
|

TMEM16A/ANO1 Inhibits Apoptosis Via Downregulation of Bim Expression

Abstract: Purpose TMEM16A is a calcium-activated chloride channel that is amplified in a variety of cancers, including 30% of head and neck squamous cell carcinomas (HNSCC), raising the possibility of an anti-apoptotic role in malignant cells. The present study investigated this using a multi-modal, translational investigation. Experimental Design Combination of 1) in vitro HNSCC cell culture experiments assessing cell viability, apoptotic activation, and protein expression 2) in vivo studies assessing similar outcome… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 24 publications
3
36
0
Order By: Relevance
“…Recently, it is reported that ONC201 could induce apoptosis by increasing the levels of Bim in myeloma cells [47], AZD9291 (the third generation EGFR inhibitor) could increase the expression of Bim by MEK/ERK-dependent pathway in EGFR-mutant non-small cell lung cancer (NSCLC) cells [48], and the combination of pimasertib (MEK inhibitor) with SAR405838 (MDM2 inhibitor) could induce the expression of Bim in vitro and in vivo in KRAS mutant non-small cell lung cancers (NSCLC) and colorectal carcinomas with wild-type TP53 [49]. TMEM16A/ANO1, as a contributor to tumor progression, could inhibit apoptosis via down-regulation of Bim expression [50]. These reports show that Bim may play a critical role in anti-tumor treatment, and may be a new target for clinical cancer therapy strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it is reported that ONC201 could induce apoptosis by increasing the levels of Bim in myeloma cells [47], AZD9291 (the third generation EGFR inhibitor) could increase the expression of Bim by MEK/ERK-dependent pathway in EGFR-mutant non-small cell lung cancer (NSCLC) cells [48], and the combination of pimasertib (MEK inhibitor) with SAR405838 (MDM2 inhibitor) could induce the expression of Bim in vitro and in vivo in KRAS mutant non-small cell lung cancers (NSCLC) and colorectal carcinomas with wild-type TP53 [49]. TMEM16A/ANO1, as a contributor to tumor progression, could inhibit apoptosis via down-regulation of Bim expression [50]. These reports show that Bim may play a critical role in anti-tumor treatment, and may be a new target for clinical cancer therapy strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Together, these findings suggest that the CCND1 , CTTN and ANO1 genes within the 11q13 amplicon could play a significant role in HPV-negative tumors but not in HPV-positive tumors. Given that 11q13 amplification has been associated with poor prognosis in HNSCC patients, and, in particular, these three genes have been involved in tumor progression and resistance to radio-, chemotherapy [11,22,23,24,25,26], and EGFR-targeted therapies [27], the herein found distinctive molecular alterations presumably could contribute to the clinical and biological differences between these two different HNSCC subtypes and explain the better prognosis and response to radiotherapy and chemotherapy associated to HPV-positive tumors. In fact, we proved the impact of these molecular alterations on patient survival.…”
Section: Discussionmentioning
confidence: 99%
“…Ion channels in general, and Ca 2+ -activated chloride channels in particular, are known to be involved in the regulation of cell proliferation, cell migration and metastasis and are believed to be important emerging drug targets in cancer (2,3). A calcium-dependent chloride channel, TMEM16A, has also been proposed to contribute to tumor growth and invasion in lung cancer, prostate cancer and head and neck squamous cell carcinomas (26)(27)(28)(29). Since CLCA1 has been demonstrated to be a direct modulator of TMEM16A, its role in tumorigenesis is increasingly recognized.…”
Section: Role In Cancermentioning
confidence: 99%